Thermal performance enhancement of solar air heater using louvered fins collector. (June 2022) - Chand, Subhash; Chand, Prabha; Kumar Ghritlahre, Harish
Highlights: An experimental model used to evaluate the thermal performance of louvered finned solar air heater. Experiment conducted from mass flow rate 0.0070 to 0.0158 kg/s. Addition of louvered fins to the absorber plate shows a significant improvement in the thermal performance. Maximum thermal efficiency achieved for louvered fin is 70% at mass flow rate 0.0158 kg/s. Abstract: Solar air heater is one of the important device for heating the air which is mainly used for space heating, timber seasoning, crop/vegetable drying, etc.. To improve the performance of solar air collectors, the fin plays an important role to increases the performances. Due to this reason in the present work, a novel type of solar air heater has been constructed with louvered fins and performed experiments to evaluate its thermal performance. The louvered fins have been attached to the bottom of the absorber plate to steer the flowing air and increase the heat transfer rate. To achieve this aim, the solar collector has been designed with the value of louvered angle, louvered length, louvered pitch & height taken to be 20°, 2.5 cm, 2.5 cm, and 3.5 cm, respectively, and conducted experiments with mass flow rate 0.007 kg/s to 0.0158 kg/s. The variations of insolation and fin spacing on the thermal efficiency and temperature rise have been also studied in the present experimental study. The results indicate that thermal efficiency increase with increasing flow rate, for a mass flow rate of 0.0158 kg/s and 0.007 kg/s, thermal efficiency and outlet temperature obtained a maximum of 70% and 58.66 °C respectively for spacing of 2 cm. further, observed that the thermal efficiency of louvered fin spacing 2 cm and 5 cm is higher as compared to plane solar air heater which is 106.7% and 59.45% respectively. The thermal performance of the louvered fins solar air heater is significantly enhanced as compared to that of the plane solar air heater.